Acts of Violence Against Journalists in Gorontalo: Problematika & Countermeasures - Feby Nur Gojali (Estudiante Law Journal, 2019)
Legally formal journalists get guaranteed legal protection in carrying out their duties, but in practice on the ground until now there is still violence against journalists or journalists in Gorontalo Province. The purpose of this study was to find out how to review violence on journalists in Gorontalo and to find out the problems and countermeasures by the Alliance of Independent Journalists (AJI) and the Gorontalo Regional Police. Based on the title raised in this study, researchers use this type of empirical legal research through primary data sources, namely data based on information obtained directly in the location of research from related parties in the form of events. The results showed that the factors behind the violence against journalists in Gorontalo were the lack of understanding of sources and journalists to the Press Code of Ethics, as for AJI's efforts in tackling violence against journalists in Gorontalo, namely, there were efforts before and after cases of violence against journalists, and there were efforts from the police by mediating and legal process.